ANALISIS EFISIENSI EKONOMI USAHATANI PADI ORGANIK DAN KONVENSIONAL DI KABUPATEN TASIKMALAYA - Nurlela Machmuddin; Nunung Kusnadi; Yusman Syaukat (Forum Agribisnis, 2016)
The purpose of  this study was to analyze the economic efficiency of organic rice farming compared conventional rice farming. This study conducted using a cross section data from 100 farmers in Tasikmalaya  Regency. The farmers are selected using proportionate stratified random sampling technique which is divided into equal size of two levels. Study was performed using stochastic frontier production function and estimated by Maximum Likelihood Estimation (MLE) method.  The result showed that the mean economic efficiency of the organic farmers (0,53) is higher compared conventional farmers (0.43). Cost saving of seed and high production in organic farming as a source of gain in economic efficiency. Knowledge on the factors influencing  farm efficiency is crucial for policy makers to improving efficiency levels.